Insulin Rescues Impaired Spermatogenesis via the Hypothalamic-Pituitary-Gonadal Axis in Akita Diabetic Mice and Restores Male Fertility - Schoeller, Erica L. (American Diabetes Association, 2012)
The mechanism responsible for poor reproductive outcomes in type 1 diabetic males is not well understood. In light of new evidence that the Sertoli cells of the testis secrete insulin, it is currently unclear whether diabetic subfertility is the result of deficiency of pancreatic insulin, testicular insulin, or both. In this study, the Akita mouse diabetic model, which expresses a mutant, nonfunctional form of ins2 in testes and pancreas, was used to distinguish between systemic and local effects of insulin deficiency on the process of spermatogenesis and fertility. We determined that Akita homozygous male mice are infertile and have reduced testis size and abnormal morphology. Spermatogonial germ cells are still present but are unable to mature into spermatocytes and spermatids. Exogenous insulin treatment regenerates testes and restores fertility, but this plasma insulin cannot pass through the blood-testis barrier. We conclude that insulin does not rescue fertility through direct interaction with the testis; instead, it restores function of the hypothalamic-pituitary-gonadal axis and, thus, normalizes hormone levels of luteinizing hormone and testosterone. Although we show that the Sertoli cells of the testis secrete insulin protein, this insulin does not appear to be critical for fertility.